A STRATEGY HOW ISLAMIC EDUCATION INSTITUTION TO BE EXCELLENT SCHOOL - Rosyidah, Emi; Rohmawati, Eti (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
Excellent Islamic educational institutions still leave questions whether from the building, infrastructure or excellent from the management process. Islamic school system in Indonesia still just to be a market. Culture in Indonesia that emphasizes physicality when choosing an educational institution needs to be changed. The process of teaching learning has to be the first aim at . One way to realize the education of Islam featured with quality management integrated, which is called by a Total Quality management (TQM). TQM is a blend of all functions of the company into holistic philosophy to build the concept of quality, teamwork, productivity, understanding and customer satisfaction. There are some strategies to improve madrasah to be excellent Islamic Institutions First. Designing the model. Second, leadership excellence. Third, design human resources, especially educators. Fourth, the potential of the spiritual, intellectual, charity, skill, and good character, Fifth, how integrating the teachings of Islam and science.